ANALISIS PRAKTIK ASUHAN KEPERAWATAN DENGAN INTERVENSI TERAPI BRANDT DAROFF EXERCISE TERHADAP PENURUNAN NYERI KEPALA PADA PASIEN VERTIGO DI RUMAH SAKIT BHAYANGKARA TK.I RADEN SAID SUKANTO JAKARTA - Nenden Purwaningsih (2022)
Vertigo is a disease that attacks the body's balance system. A person with vertigo will experience many symptoms, one of which is a severe headache. Other symptoms experienced by vertigo patients are spinning head, feeling dizzy, nausea, vomiting, ringing in the ears, body instability. Headaches that are felt in vertigo patients will be different from headaches in general. In vertigo patients, the perceived headache will affect their daily activities. There are many treatments for vertigo. It can be treated pharmacologically or non-pharmacologically. For non-pharmacological treatment, namely by doing Brandt Daroff Exercise Therapy, a relaxation therapy that can help reduce headache symptoms in vertigo patients. The purpose of this innovative intervention in addition to reducing symptoms, is expected to improve the quality of life of vertigo patients for the long term. After the innovation intervention was carried out for 3 x 34 hours where 1 day was carried out 3 sessions in 1 session consisting of 5 repetitions, the results showed that patients managed with headache on vertigo initial scale of 8 decreased to 3. This proves that Brandt Daroff Exercise Therapy is effective in management of headache symptoms in vertigo patients.